Bactibilia-effect on postoperative course and outcome in patients with bilio-pancreatic diseases - Reddy, A. Dinakar; Thota, Anuroop; Harsha, Vanga Devi (International Surgery Journal, 2021)
Background: Bactibilia is detrimental to the outcomes of biliary tract surgery. The present study was undertaken to determine the microbial flora of bile and their significance to post-operative infectious complications and morbidity. Methods: A retrospective study of patients with biliopancreatic diseases who underwent surgery from Jan 2017 to March 2020 in a tertiary care hospital were analyzed. The samples were assessed for bile microbiological flora, and a search for their possible link with post-operative infectious complications and morbidity was carried out. Results: A total of 90 bile samples were assessed. The mean age of the study group was 51.8 SD-13.6 years with male predominance. Bactibilia was found in 39 cases (43.3%), mostly in patients with malignant diseases, older than 50 years and females. Escherichia coli was the most common organism. Post-operative infectious complications were seen in twenty cases, thirteen of them in bactibilia-associated patients, showing statistical significance. Statistical significance was found between the presence of pre-operative biliary stent and bactibilia and between diabetes mellitus and bactibilia. Nine out of 24 patients with comorbidities had post-operative infectious complications. No significant relationship was found between pre-operative jaundice and comorbidities with bactibilia. Conclusions: The present study showed a statistically significant relationship between the presence of pre-operative biliary stent and bactibilia and also the incidence of post-operative infectious complications and bactibilia. Microbiological analysis of bile is a valuable tool in prognosticating the post-operative complications, thereby guiding us to provide adequate therapy and helps to establish local antibiotic guidelines.